The Emergence of Unsaturated Soil Mechanics : Fredlund Volume. - Clifton, A. W. (NRC Research Press, 2000)
This publication is an assemblage of selected papers that have been authored or co-authored by D.G. Fredlund. The substance of these papers documents the milestones of both the science of unsaturated soil mechanincs and the career of the author during his tenure as a faculty member in the Department of Civil Engineering at the University of Saskatchewan, Saskatoon, Canada.